Comparison of Knotless Versus Traditional Glenoid Anchors in Early Outcomes Following Arthroscopic Shoulder Stabilization. Issue 7 (29th July 2019) - Houck, Darby A.; Hart, Jessica; Schumacher, Alexandra N.; McCarty, Eric C.; Seidl, Adam J.; Hettrich, Carolyn M.; Wolf, Brian R.; Bravman, Jonathan T.
Objectives: To compare knotless versus traditional glenoid anchors as well as use of all-suture versus non-all suture anchor material in early outcomes after arthroscopic shoulder stabilization. We hypothesize there is no difference in outcomes between anchor type or material. Methods: Patients who were prospectively enrolled in the Multicenter Orthopaedic Outcomes Network (MOON) Shoulder Group instability database completed a series of patient reported outcomes (PROs) pre and post-operatively at 2 years. At the time of surgery, physicians documented technique utilized and materials employed. The incidence of subsequent shoulder surgeries, re-dislocations or subluxations, and return to sport (RTS) were obtained. Patients were stratified by anchor type (knotless [KL] versus knotted [KT]) and then by anchor material (all-suture [AS] versus non-all suture [NS]). Bivariate analyses were performed to compare outcomes between groups, including the Wilcoxon signed-rank test and chi-square test. Results: A total of 447 patients who underwent primary arthroscopic shoulder stabilization were evaluated, with 112 patients in the KL group (90.2% male) and 335 in the KT group (82.4% male; p > .05). Then there were 70 patients in the AS group (74.3% male) and 377 in the NS group (86.2% male; p = .01). The KT group (24.6 ± 8.9 years) was significantly older than the KL group (21.3 ±7.8 years; p = .0003) while the AS group (26.8 ±9.1 years) was significantly older than the NS group (23.2 ±8.6 years; p = .003). Significantly more patients in the KL group (87.5%) underwent surgery in the beach chair (BC) position than the KT group (45.4%; p < .0001) and significantly more patients in the NS group (59.9%) underwent surgery in the BC position than the AS group (34.3%; p < .0001). The primary direction of instability was anterior, with 78.6% in the KL group, 71.3% in the KT group, 82.9% in the AS group and 71.4% in the NS group. The number of contact athletes was similar in each group, with 75.0% in the KL group, 66.0% in the KT group, 70.0% in the AS group, and 67.9% in the NS group. Significantly more anchors were used in the KL group (4.2 ± 1.6) compared to the KT group (3.9 ± 1.8; p = .003) and significantly more anchors were used in the AS group (5.3 ± 2.4) compared to the NS group (3.7 ± 1.4; p < .0001). Significantly more patients had a redislocation in the KL group (11.6%) compared to the KT group (5.7%; p = .03), and significantly more patients had a redislocation in the NS group (8.2%) compared to the AS group (1.4%; p = .04). There were no significant differences in improvement of any PROs, incidence of RTS, subsequent shoulder surgeries or subluxations between anchor type or material groups. Conclusion: Compared to traditional knotted glenoid anchors, patients undergoing arthroscopic shoulder stabilization with knotless anchors can expect to experience similar clinical outcomes. However, use of knotless anchors may be a significant risk factor for subsequent dislocation 2 years after arthroscopic shoulder stabilization surgery, which may be related to patients' age. Moreover, use of all-suture based anchors may be associated with lower rates of subsequent dislocation which may be attributed to the size of their footprint and the apparent inclination of surgeons using these to utilize more anchors per labral repair, thus increasing points of labral fixation. Continued investigation of potential confounding variables is necessary to identify the direct effect of anchor type and material on patient outcomes.